2017
DOI: 10.1037/adb0000266
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental origins of gambling behaviors from ages 18 to 25: A longitudinal twin family study.

Abstract: Gambling behaviors tend to increase in prevalence from late adolescence to young adulthood, and the underlying genetic and environmental influences during this period remain largely understudied. We examined the genetic and environmental influences on gambling behaviors contributing to stability and change from ages 18 to 25 in a longitudinal, behavioral genetic mixed-sex twin study design. Participants were enrolled in the Minnesota Twin Family Study. A range of gambling behaviors (maximum frequency, average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…2 In the Minnesota study, there were significant genetic influences on variation in typical frequency at ages 18 and 25 years. There was a substantial and significant contribution of the shared environment only at age 18 years (King et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In the Minnesota study, there were significant genetic influences on variation in typical frequency at ages 18 and 25 years. There was a substantial and significant contribution of the shared environment only at age 18 years (King et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 279 13-year-old Quebec twin pairs, gambling involvement was completely explained by genetic and unique environmental factors, with no contribution from the shared family environment (Vitaro et al, 2014). A study of 756 Minnesota twin pairs assessed at ages 18 and 25 years reported results for several measures of gambling, including one 'typical frequency' similar to the measure used in the Quebec study (King et al, 2017). 2 In the Minnesota study, there were significant genetic influences on variation in typical frequency at ages 18 and 25 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other study was based on data collected within the context of an ongoing longitudinal twin study in Minnesota (King et al, 2017). At ages 18 and 25, participants completed questionnaires of past-year symptoms of GD as measured by the South Oaks Gambling Screen (Lesieur and Blume, 1987).…”
mentioning
confidence: 99%
“…Estimates of the contribution of genetic factors to variation in GD were 5–37%, varying by age and sex, with genetic contributions increasing over time for men and decreasing over time for women. Additionally, there was evidence of significant shared environmental influences (19–29%) at age 18 (King et al ., 2017). These discrepant findings might be due to the relative youth of this sample, the low yield of gambling problems, or the focus on past-year rather than lifetime pathology.…”
mentioning
confidence: 99%